Formulation and Evaluation Of Sunscreen Foundation Cream Containing Jackfruit Seed (Artocarpus heterophyllus L.) Extract As A Natural Uv Protective Agent - Siti Muliani Julianty Siti; Salmah Handayani Lubis Lubis; Jenti Najira Siregar Jenti (Jurnal FARMASIMED (JFM), 2026)
Background: The utilization of natural ingredients in the cosmetic industry has increased significantly as consumers tend to prefer products that are safe and environmentally friendly. Jackfruit seeds (Artocarpus heterophyllus L.) are known to contain various bioactive compounds, including alkaloids, flavonoids, saponins, and tannins, which are reported to have potential photoprotective properties against ultraviolet (UV) radiation. Objective: This study aimed to evaluate the potential of ethanol extract from jackfruit seeds as an active ingredient in the formulation of a foundation cream with sunscreen activity based on the Sun Protection Factor (SPF) value. Methods: This research employed a laboratory-based experimental approach. The jackfruit seed simplicia were first dried and then extracted using analytical grade ethanol (p.a.). The obtained extract was subjected to phytochemical screening to identify the presence of secondary metabolites. Furthermore, the extract was formulated into foundation cream preparations with concentrations of 2%, 4%, and 6%. The prepared formulations were evaluated through several parameters including homogeneity, pH, spreadability, adhesion, and  determination of SPF values using a UV-Vis spectrophotometer. Results: Phytochemical screening results indicated that the ethanol extract of jackfruit seeds contained alkaloids, flavonoids, saponins, and tannins. All formulations produced homogeneous preparations with pH values ranging from 4.5 to 6.5. The spreadability values were within the range of 6.0–6.7 cm, while adhesion ranged from 7.97 to 11.63 seconds, which met the standard requirements for topical preparations. The SPF values increased proportionally with the extract concentration, showing values of 0.816 for the blank formulation, 4.38 for F1, 5.92 for F2, and 6.52 for F3. Conclusion: The ethanol extract of jackfruit seeds demonstrated potential as an active ingredient in foundation cream formulations with sunscreen activity. These findings indicate an opportunity for the development of innovative natural-based cosmetic products that provide protective effects against ultraviolet radiation.